2016
DOI: 10.3402/jchimp.v6.31950
|View full text |Cite
|
Sign up to set email alerts
|

Solitary parotid metastasis 8 years after a nephrectomy for renal cell carcinoma

Abstract: Renal cell carcinoma is a common cancer, known for its aggressive behavior and ability to metastasize nearly every organ system in the body. While the cancer commonly spreads to a select few organs and metastasis usually develops within 5 years of diagnosis, there have been numerous case reports of atypical sites of metastasis and cases of relapse up to decades after treatment. We present a case a 65-year-old male who presented with right preauricular swelling 8 years after the initial diagnosis and right neph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…These factors together contribute to the unique hematogenous route of spread of renal cell carcinoma as a tumor thrombus into the lumen of the inferior vena cava ( 7 ). The other route of spread is the lymphatic system ( 3 ). The usual sites of metastases are the lung, liver, brain, and bone ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These factors together contribute to the unique hematogenous route of spread of renal cell carcinoma as a tumor thrombus into the lumen of the inferior vena cava ( 7 ). The other route of spread is the lymphatic system ( 3 ). The usual sites of metastases are the lung, liver, brain, and bone ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the first choice in the diagnosis of parotid swellings is ultrasonic examination ( 7 ). The diagnostic value of fine-needle aspiration biopsy (FNAB) is controversial, as it is associated with a high false-negative rate in the evaluation of metastatic renal cell carcinoma to the parotid gland; this is contributed its vascular nature ( 3 , 10 , 11 ). Pathological examination, immunohistochemical staining with antibodies against CD10, CEA, EMA, CK, and vimentin, are essential even if FNAB is diagnostic ( 3 , 7 , 9 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first cases of parotid involvement due to RCC metastases were reported by Patey et al in 1965 7 . Since then, there have been limited reported cases of this phenomenon 6,[8][9][10][11][12][13][14][15][16] . In their review of the literature, Lawlor et al reported 45 cases of RCC metastasizing to the parotid, of which only 31 were complete case presentations 6 .…”
Section: Discussionmentioning
confidence: 99%